Pengaruh Kegel Exercise dan Menopause Massage terhadap Fungsi Seksual Wanita Perimenopause - Prastiwi, Dani; Vianti, Remilda Armika; Susanti, Nur; Barokatazzahro, Abroza; Hawa, Irena Tri (Poltekkes Kemenkes Bengkulu, 2024)
Perimenopause causes sexual dysfunction. Kegel exercise and menopause massage as non-pharmacological therapy to overcome sexual function problems. This research was conducted to determine the effect of sexual function on perimenopauseal women before and after being given Kegel exercise and menopause massage. This research used pre experimental research with a one group pretest and posttest design as the method. The sample was selected according to the criteria set by researchers, namely women of childbearing age who have a partner (husband), aged 40-45 years, are sexually active and can carry out independent activities. There were 30 participants as research samples in Bandengan Village, Pekalongan City. Sexual function data was collected using the Female Sexual Function Index (FSFI) questionnaire. The results of this study, before the Kegel exercise and menopause massage were carried out, the number of respondents who experienced sexual dysfunction was 63.30% and after being given intervention it fell to 56.70% with a significance value of 0.430. Can be concluded that there is no effect of Kegel exercise and menopause massage on sexual function. However, whem viewed based on the FSFI domain, the overall FSFI domain experienced an increase in average after being given Kegel exercise and menopause massage interventions. In theory, Kegel exercises and menopausal massage have benefits that can improve sexual function, so the commitment of perimenopausal women is needed.